New Identity of Russian Speaking Children in Estonian Society - Mare Leino (Social Work & Society, 2006)
According to Estonian Statistical Office whether we take the number of grade repeaters, the number of graduates or the number of students graduating with a distinction as a basis for the analysis, the academic achievement incline has remained the same for several years - girls whose language of instruction is Russian come at the top, followed by girls who study in Estonian. Boys come last, and boys studying in Russian reveal much better results than boys whose language of instruction is Estonian (Heinlo 2001, 23). Current paper is going to show that native Estonians have problems as well and starting from school already; Russian speaking youth is doing even better (with hard work). So the question is: who is the better citizen - a native but quite easy-going, or an (former) immigrant who is eager? In European social thought the concept of citizenship is constructed as universal, but it contains tensions between sameness and difference, us and others, centres and margins (Gordon et al 2000, 9). For us citizenship means belonging, which means safety. Here we will ask: is it (for better future) enough just to be a native Estonian, or should one work for ones success as much as many immigrants do.